Biotribological screening of amorphous carbon coatings on hard-on-soft pairings for total knee arthroplasty - Neusser, Kevin; Rothammer, Benedict; Marian, Max; Bartz, Marcel; Wartzack, Sandro (5th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2022)
The purpose of endoprosthetic joint replacement is to regain the functionality and allow patients to live a more mobile and pain-free life. Aseptic loosening of total knee arthroplasty (TKA) is a major cause of premature failure, with wear particles removed from the implant materials being largely responsible. Therefore, great efforts are being made to reduce the wear of polymer inlays by surface modifications. This study concentrates on the screening of the effectiveness of wear-reducing amorphous carbon coating systems on hard-on-soft pairings (metal-on-polymer). The biotribological behavior of the uncoated and coated pairings is investigated using a climate- and stress-controlled rheometer supplemented with a tribo-cell in a polyethylene ball and three metallic pins configuration, lubricated with diluted bovine calf serum (BCS) at 37 °C, in oscillatory sliding mode. The frictional behavior is analyzed in-situ while the wear performance is characterized ex-situ using light microscopy and laser scanning microscopy. This screening reveals the applicability of amorphous carbon coatings to the considered materials used for biomedical applications. It demonstrates the potential for wear reduction and forms a basis to determine the most promising of the deposited diamond-like carbon (DLC) coatings, therefore allowing for more focused research in the development of tribologically effective coating system